Guideline gynekologických zhoubných nádorů 2004--Primární komplexní lécba operabilnich stadií zhoubných nádorů vulvy - Robová, H; Rob, L; Svoboda, B; Stankusová, H; Cwiertka, K; Neumannová, R; Petera, J; Koliba, P; Dörr, A; Onkogynekologická sekce, Ceska onkologická a porodnická spolecnost (Ceska gynekologie, 2004)
OBJECTIVE: Elaboration of guideline for primary treatment of operable vulvar cancer. DESIGN: Review, consensus between proposers and opponents. SETTING: Department of Obstetrics and Gynecology, 2nd Medical Faculty Charles University and Faculty Hospital Motol, Prague. METHOD: A retrospective review of published data, analysis of Czech statistics and consensus between proposers and opponents. RESULTS: Guideline for the diagnosis remain the same as in the proposal from 1998. We elaborated practically new guideline for surgical treatment. Wide excision or simplex vulvectomy is adequate only for stage la without angioinvasion, free margins have to be 5 mm. Standard surgical procedure is radical vulvectomy with inquinofemoral lymphadenectomy in stage 1a with angioinvasion, 1b and 2. In laterally localised lesions it is possible to perform hemivulvectomy or radical excision with inquinofemoral lymphadenectomy. Free margins have to be more than 8 mm. An alternative procedure in internally high-risk patients is sentinel node detection with radical vulvectomy (hemivulvectomy). Sentinel node detection has to by performed by combined method of blue dye and radiocoloid Tc 99 simultaneously. Bilateral inquinofemoral lymphadenectomy is indicated in case of positive sentinel node. Primary radiotherapy is indicated in higher stages, in stage 3 we can perform an exenteration with the agreement of patient. CONCLUSION: Guideline for the treatment of vulva cancer should be directions for clinicians and others, who participate in the process of treatment of the vulva cancer. Guidelines include all parts of the process (from diagnosis to follow up). All topics of the guidelines were arise from a voting of the proposers and opponents.
Keywords: Vulvar Neoplasms; Female; kombinovaná terapie; nádory vulvy; Humans; Combined Modality Therapy; ženské pohlaví; lidé